Demographic trends and housing patterns in the Philippines - Marife Magno-Ballesteros; Jenica A. Ancheta; Tatum P. Ramos (Philippine Institute for Development Studies (PIDS), 2024)
This study examines how demographic changes lead to different household structures and housing choices among different age groups. It argues that the cointegration of demography, housing market, and wealth have shaped housing demand in the country over time. The results have important often unrecognized implications for housing policy. The estimation of housing needs that excludes a contextual analysis of household formation can be misleading, thus the government has to connect the demographic changes to housing demand to ensure that the correct policy framework is provided that will balance the needs of the productive sector and those of the growing elderly population with housing consumption.
Keywords: 330; demographic trends; household formation; homeownership; housing habitability; Philippines